The Developmment of the Assessment's Instrument Based on Higher Order Thinking Skills To Measure Dimension of Persuasive Text Skills on Students Of Class VIII in Junior High School Muhammadiyah 7 Medan - Indah Fajarini; M. Oky Fardian Gafari; Abdurahman Adisaputera (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research deals with the development of the assessment’s instrument based on higher order thinking skills to measure dimension of persuasive text skills on students of class VIII in junior high school Muhammadiyah 7 Medan. The type of this research is research and development. The sampling technique used in this study is purposive sampling technique. The result shows that the process of developing assessment instruments is based on Higher Order Thinking Skills on Indonesian language subjects in junior high school Muhammadiyah 7 Medan through 4 stages, there are: (1) Preparation of Tests, (2) Selection of Media (3) Selection of Formats (4) Initial design results by composing stories board, make layouts by paying attention to the color and composition and fill the layout with activities in the form of, activity 1 contains the mapping of KI, KD, and indicators, as well as 10 multiple choice questions and 5 description questions. Activity 2 contains the mapping of KI, KD, and indicators as well as 15 multiple choice questions and 5 description questions and scoring, answer keys, glossary and bibliography.